Sex prediction using palatal surface of maxillary permanent lateral incisors - Yi, Ethel Lim (Universiti Sains Malaysia, 2025)
Sex determination is a crucial aspect of forensic anthropology and human identification, aiding in narrowing down potential identities in forensic investigations. This study aimed to assess the potential of using the palatal surface area (PSA) and mesiodistal (MD) dimension of the maxillary lateral incisor for sex prediction within the Malay population (Malaysian). A total of 100 dental casts (50 males and 50 females) were analysed using 3D imaging software (3-Matic-Mimics, Materialise, Belgium), and statistical analyses were conducted to determine the presence of sexual dimorphism and the predictive accuracy of these dental features. The results indicated that the PSA of the maxillary lateral incisor exhibited statistically significant sexual dimorphism, with males having a larger mean PSA than females (p < 0.05). However, the MD dimension did not show a significant difference between sexes (p > 0.05). Logistic regression analysis identified PSA as a significant predictor for sex classification, but the overall classification accuracy of the model was 61%, with 60.0% accuracy for males and 62.0% for females. The area under the receiver operating characteristic (ROC) curve (0.39) further indicated a poor discriminative ability of the model. These findings suggest that the PSA of the maxillary lateral incisor only moderately predict sex, thus has limited application in forensic management.